Aging is associated with impaired angiogenesis, but normal microvascular network structure, in the rat mesentery - Sweat, Richard S. (Am J Physiol Heart Circ Physiol, 2017)
A big problem associated with aging is thought to be impaired microvascular growth or angiogenesis. However, to link the evidence for impaired angiogenesis to microvascular dysfunction in aged tissues, we must compare adult vs. aged microvascular networks in unstimulated scenarios. The objective of this study was to test the hypothesis that aged microvascular networks are characterized by both fewer vessels and the impaired ability to undergo angiogenesis. Mesentery tissues from adult (9-mo) and aged (24-mo) male Fischer 344 rats were harvested and immunolabeled for platelet/endothelial cell adhesion molecule (an endothelial cell marker) according to two scenarios: unstimulated and stimulated. For unstimulated groups, tissues harvested from adult and aged rats were compared. For stimulated groups, tissues were harvested 3 or 10 days after compound 48/80-induced mast cell degranulation stimulation. Unstimulated aged microvascular networks displayed larger mean vascular area per tissue area compared with the unstimulated adult networks. The lack of a decrease in vessel density was supported at the gene expression level with RNA-Seq analysis and with comparison of vessel densities in soleus muscle. Following stimulation, capillary sprouting and vessel density were impaired in aged networks at 3 and 10 days, respectively. Our results suggest that aging associated with impaired angiogenesis mechanisms might not influence normal microvascular function, since unstimulated aged microvascular networks can display a “normal adult-like” vessel density and architecture. NEW & NOTEWORTHY Using a multidimensional approach, we present evidence supporting that aged microvascular networks display vessel density and patterning similar to adult networks despite also being characterized by a decreased capacity to undergo angiogenesis. Thus, vessel loss is not necessarily a characteristic of aging.